Vector Mechanics for Engineers Statics and Dynamics - R.Eisenberg Elliot (McGraw-Hill Higher Education, 2007)
This is really a great book in a hard to grasp subject.It is easy to follow ,has a lot of excellent sample problems and examples ,student-friendly and it is ideal for selfstudy.